Pengembangan Kampung Tempe dalam Pemasaran melalui Media Online Berbasis Web - Moch. Djauhari (LPPM Stikosa - AWS, 2021)
During this pandemic, MSME entrepreneurs experienced a decline in sales, especially MSMEs in Tempe Village. This tempe village has a community to protect these soybean processed producers. During this pandemic period, the community stopped and was not active, at least 5 people were still actively producing processed soybeans. This tempe village produces various processed tempeh such as tempe chips, botok tempeh, tempeh jes, soybean juice, etc. During this pandemic, the results from the sale of processed products in Tempe Village have decreased. Therefore, the researcher in this group 17 Field Work Lecture wants to help optimize the marketing of this tempe village in order to obtain maximum income. Through the introduction and use of online media to producers in this tempe village. In addition, it also provides education to producers in this tempe village regarding the use of this online media. This study uses descriptive research methods with data collection techniques through direct observation and interviews with tempe producers in Tempe Tenggilis Village. The data that the researchers obtained was that during this pandemic, processing activities in the tempe village decreased drastically, previously they could produce 100 kg per day, now they only produce about 60 kg per day. Through the Field Work Lecture that we will do on May 24 to July 9, 2021 researchers try to help promote Kampung Tempe via the Web.